3D Organoid Culture From Adult Salivary Gland Tissues as an ex vivo Modeling of Salivary Gland Morphogenesis - Kim, Donghyun; Yoon, Yeo-Jun; Choi, Dojin; Kim, Jisun; Lim, Jae-Yol (Frontiers in Cell and Developmental Biology, 2021)
Lumen formation of salivary glands has been investigated using in vivo or ex vivo rudiment culture models. In this study, we used a three-dimensional (3D) salivary gland organoid culture system and demonstrated that lumen formation could be recapitulated in mouse SMG organoids. In our organoid culture system, lumen formation was induced by vasoactive intestinal peptide and accelerated by treatment with RA. Furthermore, lumen formation was observed in branching duct-like structure when cultured in combination of fibroblast growth factors (FGF) in the presence of retinoic acid (RA). We suggest RA signaling-mediated regulation of VIPR1 and KRT7 as the underlying mechanism for lumen formation, rather than apoptosis in the organoid culture system. Collectively, our results support a fundamental role for RA in lumen formation and demonstrate the feasibility of 3D organoid culture as a tool for studying salivary gland morphogenesis.